1990
DOI: 10.1063/1.103343
|View full text |Cite
|
Sign up to set email alerts
|

Formation of arsenic precipitates in GaAs buffer layers grown by molecular beam epitaxy at low substrate temperatures

Abstract: We have grown film structures by molecular beam epitaxy which include GaAs buffer layers grown at low substrate temperatures (250°C). The film structures have been examined using transmission electron microscopy. The layers grown at normal temperatures (600 °C) were free of defects or clusters. In contrast, the layer which 'Nas grown at low substrate temperatures contained precipitates which have been identified as hexagonal arsenic. The density of the arsenic precipitates is found to be very sensitive to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(63 citation statements)
references
References 11 publications
4
58
0
1
Order By: Relevance
“…LTG-GaAs is prepared through molecular beam epitaxial growth at 200 °C instead of the usual 600 °C. After growth, however, proper in situ or ex situ annealing at 600 °C is necessary in order increase the density of arsenic precipitates and hence resistivity of this layer [60]. A high density (>10 18 cm -3 ) of arsenic precipitates in LTG-GaAs results in excess arsenic-related point defects and a short carrier trapping time [61].…”
Section: Millimeter-wave Photonic Transmittersmentioning
confidence: 99%
“…LTG-GaAs is prepared through molecular beam epitaxial growth at 200 °C instead of the usual 600 °C. After growth, however, proper in situ or ex situ annealing at 600 °C is necessary in order increase the density of arsenic precipitates and hence resistivity of this layer [60]. A high density (>10 18 cm -3 ) of arsenic precipitates in LTG-GaAs results in excess arsenic-related point defects and a short carrier trapping time [61].…”
Section: Millimeter-wave Photonic Transmittersmentioning
confidence: 99%
“…Subsequent annealing of these layers above 400°C in As ovetpressure results in a uniform semi-insulating property and the lowering of their lattice parameter to the value of stoichiometric GaAs grown at normal temperatures (-600°C). Transmission electron microscopy (TEM) investigation revealed that As precipitates with diameter ranging from 2 to 5 nm are formed in the layers after annealing [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…GaAs thin films grown by Molecular Beam Epitaxy (MBE) at low growth temperature,T g (<400°C) have been subject to many investigations recently [1][2][3][4][5][6][7][8][9][10]. Murotani et.al.…”
Section: Introductionmentioning
confidence: 99%
“…5 With anneal this excess arsenic beings to precipitate. 6 The final composite structure of semimetallic arsenic precipitates in a GaAs matrix can be controlled with the substrate temperature during MBE and the subsequent anneal. The substrate temperature during MBE sets the amount of excess As in the epilayer; 7,8 the subsequent anneal controls the precipitation of the excess arsenic and the amount of coarsening of the arsenic precipitates.…”
mentioning
confidence: 99%